Prevalence of undernutrition among adult tuberculosis patients in Ethiopia: A systematic review and meta-analysis - Wondmieneh, Adam (J Clin Tuberc Other Mycobact Dis, 2020)
BACKGROUND: Undernutrition and tuberculosis are the major public health problems of people living in middle and low-income countries. Even though single studies have been reported from different areas of Ethiopia, there is no national-level study that estimates the overall burden of undernutrition among tuberculosis patients. Therefore, this study aimed to estimate the overall magnitude of undernutrition among adult tuberculosis patients in Ethiopia. METHODS: We searched out records from databases such as PubMed/MEDLINE, HINARI, EMBASE, Scopus, Google Scholar, and African journals and the online Ethiopian University repositories for published and unpublished articles. The data were extracted using a standardized data extraction format. Meta-analysis was computed using STATA version 11 software. The Cochrane Q-test and I(2) with its corresponding p-value were used to assess the heterogeneity of the study. The presence of publication bias was evaluated using Egger’s test and presented with funnel plots. The random-effects meta-analysis model was computed to estimate the pooled prevalence of undernutrition among adult tuberculosis patients. RESULTS: A total of Twelve observational studies with 4963 study participants were included in this systematic review and meta-analysis. The pooled prevalence of undernutrition among tuberculosis patients in Ethiopia was 50.8% (95% CI 43.97, 57.63). The results of subgroup analysis showed that the highest prevalence of undernutrition among TB patients was observed from studies done in the Amhara region (65.63%). In this meta-analysis, the pooled prevalence of undernutrition among TB-HIV co-infected patients was 45.45% (95%CI 21.85, 56.07). CONCLUSION: The prevalence of undernutrition among TB patients in Ethiopia was noticeably high. The result of this study showed that undernutrition is more severe in the Amhara regional state. Additionally, TB-HIV co-infected patients are highly affected by undernutrition. Therefore, the Ministry of Health in collaboration with clinicians should give special attention to provide nutritional care and support for TB patients as part of regular care. Moreover, special nutritional support should be designed for TB-HIV co-infected patients.